A New Model For Endocrine Glucose-Insulin Regulatory System - Al-Hussein, Abdul-Basset A.; Tahir, Fadhil Rahma (Iraqi Journal for Electrical and Electronic Engineering, 2020)
To gain insight into complex biological endocrine glucose-insulin regulatory system where the interactions of components of the metabolic system and time-delay inherent in the biological system give rise to complex dynamics. The modeling has increased interest and importance in physiological research and enhanced the medical treatment protocols. This brief contains a new model using time delay differential equations, which give an accurate result by utilizing two explicit time delays. The bifurcation analysis has been conducted to find the main system parameters bifurcation values and corresponding system behaviors. The results found consistent with the biological experiments results.